Characterization of the intrahospital transport of critically ill patients - Meneguin, Silmara [UNESP]; Correa Alegre, Patricia Helena; Luppi, Cláudia Helena Bronzatto [UNESP] (Univ Fed São Paulo, Dept Enfermagen, 2014)
Objective: Characterizing the transport of critically ill patients in an adult intensive care unit.Methods: Cross-sectional study in which 459 intra -hospital transports of critically ill patients were included. Data were collected from clinical records of patients and from a form with the description of the materials and equipment necessary for the procedure, description of adverse events and of the transport team.Results: A total of 459 transports of 262 critically ill patients were carried out, with an average of 51 transports per month. Patients were on ventilatory support (41.3 %) and 34.5 % in use of vasoactive drugs. Adverse events occurred in 9.4% of transports and 77.3 % of the teams were composed of physicians, nurses and nurse technicians.Conclusion: The transport of critically ill patients occurred in the morning period for performing computerized tomographies (CT scans) with patients dependent on mechanical ventilation and vasoactive drugs. During the transports the equipment was functioning, and the adverse events were attributed to clinical changes of patients.
Caracterização do transporte de pacientes críticos na modalidade intra-hospitalar
Keywords: Transportation of patients; Patient transfer; Critical care; Inpatient; Patient care team